PENGARUH KUALITAS JASA AUDIT TERHADAP LOYALITAS KLIEN DENGAN MEDIATOR KEPUASAN KLIEN (Students' Journal of Accounting and Banking, 2013)
This study aims to examine whether the quality of audit services with 5 dimensions namely tangible, reliability, responsiveness, assurance, empathy having an influence on client satisfaction, client satisfaction influences customer loyalty and client satisfaction as a mediator of quality of audit services as mediator of quality audit services to the client loyalty.The population in this study is a manufacturing and service company located in Central Java, while the sample of this study is the manufacturing and service company located in Central Java, which have been audited by KAP. Data used in this study is primary data, the method of data collection questionnaire. Technical analysis using multiple regression.Results of this study indicate that service quality had no significant effect on client satisfaction. While client satisfaction and quality of audit services of the dimensions reliability, assurance, empathy significant effect on client loyalty.Keywords: Quality audit services, client satisfaction, client loyalty.